Policy-influencer perspectives on the development, adoption, and implementation of provincial school-based daily physical activity policies across Canada: A national case study. (August 2020) - Campbell, Elizabeth J.; Lee Olstad, Dana; Spence, John C.; Storey, Kate E.; Nykiforuk, Candace I.J.
Abstract: Objectives: School-based daily physical activity (DPA) policies represent a promising intervention for increasing physical activity levels among children. Between 2005 and 2010, five Canadian provinces adopted and implemented DPA policies. This national case study explored facilitators and challenges to developing, adopting and implementing DPA policies from the perspective of key stakeholders ('policy-influencers') in these five provinces. Methods: Development, adoption and implementation of DPA policies at the provincial level was the phenomenon of interest, with each province constituting a distinct case. Semi-structured interviews were conducted with 15 purposively selected policy-influencers across the five case provinces. Cases were first analyzed separately, and then concurrently in a cross-case comparison. Qualitative content analysis was used to code interviews and develop themes. Results: Four themes related to the development, adoption, and implementation of DPA policies emerged: existing resources and capacity for policy change ; top-down policy development/adoption and bottom-up implementation ; political will and windows of opportunity ; and, ideology and policy change . Each of these themes encompassed facilitators and challenges related to policy processes surrounding development, adoption and implementation of DPA policies. Conclusion: These findings can inform development of future health-related polices in schools. Stakeholders can, for instance, remain attuned to the opening of political windows and capitalize on them as an opportunity to advocate for policy change or create communities of practice to enhance coordination among policy stakeholders. Future studies that explore why other jurisdictions have failed to adopt DPA policies might yield novel insights regarding leverage points to support widespread diffusion of DPA policies. Highlights: Between 2005 and 2010, five Canadian provinces adopted and implemented DPA policies. A national case study explored facilitators and challenges to adopting and implementing provincial DPA policies. Four key themes related to policy change: capacity, adoption and implementation, political will, and ideology. Recommendations can inform development and implementation of school-based physical activity and health promotion policy.